2017
DOI: 10.1016/j.techfore.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

How institutional logics hamper innovation: The case of animal testing

Abstract: For radical innovation to become successful the substitution of established practices are essential. Nevertheless, in the innovation literature novelty is often at the center and only little attention is paid to the influence of established technologies and underlying routines. This paper aims to contribute to this gap by increasing the understanding about the effect of persistence of established practices on the innovation process. We do this by using a framework that combines the Technological Innovation Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
1
12
0
1
Order By: Relevance
“…Their studies are related to organisational ecology [11], innovation [53], supply chain management [12,54], and social entrepreneurship [9]. Several PBS have been done on sustainability, especially on the transition to sustainability, which is an emerging area of research [3,55,56]; there are also those that examine sustainability within the field of strategy studies [2,38].…”
Section: Discussionmentioning
confidence: 99%
“…Their studies are related to organisational ecology [11], innovation [53], supply chain management [12,54], and social entrepreneurship [9]. Several PBS have been done on sustainability, especially on the transition to sustainability, which is an emerging area of research [3,55,56]; there are also those that examine sustainability within the field of strategy studies [2,38].…”
Section: Discussionmentioning
confidence: 99%
“…These logics work interdependently to shape firms’ innovation performance. Similarly, results regarding the independent and interdependent roles (most suggest a negative role) of multiple institutional logics on innovation can also be found in various research contexts including animal testing (Kooijman, Hekkert, van Meer, Moors, & Schellekens, 2017), social entrepreneurship (Zhao & Lounsbury, 2016), and industrial and academic science (Sauermann & Stephan, 2013), among others. In sum, previous studies have suggested that multiple logics can coexist to shape firms’ innovation.…”
Section: Theory and Hypothesesmentioning
confidence: 86%
“…There is a growing literature that integrates these perspectives to shed light on the innovation process of industrial sectors or business organizations. For instance, in their study, Kooijman et al (2017) combine technological innovation systems with institutional logics perspective and reveal that the existing institutional logics might hamper the innovation process, which requires a socio-technical transition, by reinforcing the established practices and routines. In a similar vein, while the study of Turner et al (2016) shows how the prevalent institutional logics can be linked with the core blocking mechanism in an innovation system and how it can hinder the coinnovation process, the study of Cai (2015) reveals the impact of diverse institutional logics on the development of the Triple Helix innovation systems, which refer to the relationship between university, industry and government, at different national contexts.…”
Section: Integration Of Theoretical Perspectives: a Model Of Social Entrepreneurshipmentioning
confidence: 99%